(untitled) (Proceedings of the International Conference on Public Health, 2023)
LLINs are one of the interventions in malaria vector control. Although LLINs are considered effective for three years, the way in which they are used and maintained by users affects their physical and chemical durability. The purpose of this study was to determine the relationship between the level of knowledge and attitude with the practice of using and maintaining LLINs in Sidomulyo Region. The population of this study was 153 households, and the research sample was 117 households with the criteria that respondents were ≥ 17 years old and received KBTL in August - September 2022. The results showed that knowledge with p value <0,001; CC 0,351 and attitude with p value <0,001; CC 0,507 were significantly associated with the practice of using and maintaining KBTL. The physical condition of the KBTL was in the good category, with 84% in good condition and 20.5% in good condition. The analysis showed that there was a relationship between knowledge level and attitude towards the use and maintenance of the KBTL (p value <0.001); there was a relationship between knowledge level and practice towards the use and maintenance of the KBTL (p value <0.001); and there was a relationship between attitude and practice towards the use and maintenance of the KBTL (p value <0.001). It was concluded that despite having negative attitudes, respondents’ knowledge and practices related to the use and maintenance of long-lasting insecticidal nets were good enough to prevent malaria transmission.